What is a girl worth: the role of discourse in the perpetuation and obfuscation of institutional abuse in USA gymnastics - Goosen, Nicola (African Studies, 2025)
In an overcrowded Michigan courtroom in January 2018, hundreds of girls and women – most of them gymnasts – gave Victim Impact Statements speaking to the abuse they faced not only by then-defendant Larry Nassar, but by numerous coaches. Many testified to the fact that it was the culture of (USA) gymnastics, led by national team coaches Márta and Béla Károlyi and CEO Steve Penny, that not only allowed this abuse to occur but allowed it to continue despite numerous official reports on Nassar and many other coaches. This research investigates which discourses in the gymnastics world contributed to the perpetuation and obfuscation of decades-long sexual, physical, emotional, and verbal abuse by many of those in a position of power over athletes. The research was conducted through a Critical Discourse Analysis of competition commentary, interviews with coaches and gymnasts, and documentaries covering the sport. The CDA was informed by a computer-assisted corpus analysis of the data collected. It was found that various discourses surrounding weight and diet, mental fortitude, incredibly high expectations, and discourses that explicitly objectify gymnasts, contributed to the perpetuation and obfuscation of abuse at USA Gymnastics.